2012
DOI: 10.1007/s10646-012-0910-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of polar organic chemical integrative samplers to assess the effects of chronic pesticide exposure on biofilms

Abstract: The responses of aquatic organisms to chronic exposure to environmental concentrations of toxicants, often found in mixtures, are poorly documented. Here passive sampler extracts were used in experimental contamination of laboratory channels, to investigate their effects on natural biofilm communities. A realistic mixture of pesticides extracted from Polar Organic Chemical Integrative Samplers was used to expose biofilms in laboratory channels to total pesticide concentrations averaging 0.5 ± 0.1 μg l⁻¹. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In particular, high concentrations of the herbicides diuron, its main biodegradation product, 1-(3,4-dichlorophenyl)-3-methyl urea (DCPMU) and norflurazon (NFZ) have been recorded over several years at the downstream site on the river (Montuelle et al, 2010;Rabiet et al, 2010;Morin et al, 2012). Photosynthetic processes are highly sensitive to the presence of toxicants leading to an increase in their use as ecotoxicological endpoints in particular through the measurement of fluorescence parameters (Corcoll et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, high concentrations of the herbicides diuron, its main biodegradation product, 1-(3,4-dichlorophenyl)-3-methyl urea (DCPMU) and norflurazon (NFZ) have been recorded over several years at the downstream site on the river (Montuelle et al, 2010;Rabiet et al, 2010;Morin et al, 2012). Photosynthetic processes are highly sensitive to the presence of toxicants leading to an increase in their use as ecotoxicological endpoints in particular through the measurement of fluorescence parameters (Corcoll et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were performed using extracts of POCIS that trap, among other organic substances, the most hydrophilic pesticides (for a review see Harman et al 2012). More recently, it has been shown that the combination of POCIS and bioassays could be used to assess the short-term effects of extracted pesticide mixtures on phototrophic biofilm communities, opening new perspectives to implement PICT-based approaches on pesticide mixtures (Pesce et al 2011a;Morin et al 2012;Kim-Tiam et al 2014a). One advantage of such an approach, besides considering mixtures, is that there is no need to make an a priori selection of the pesticides tested, thus giving an estimation of an integrative measure of the toxic potential of a group of compounds including unknown toxicants and metabolites, which are usually overlooked in ecotoxicological studies, especially when assessing effects at the community level (Pesce et al 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…Pesticide mixture was extracted as previously described (Pesce et al 2011a) from six "Accumulative" POCIS (Morin et al 2012). Metal mixture was extracted from the resin-gel layer of 24 DGTs with 1 M HNO 3 (Suprapur, Merck), and DGT acid extracts were neutralized with NaOH (Suprapur, Merck) prior to assessing its toxicity as in Roig et al (2011).…”
Section: Short-term Toxicity Tests With Toxicant Mixtures Extracted Fmentioning
confidence: 99%
“…POCIS extracts were used to assess the impacts of environmental pesticide mixtures with ecologically relevant bioassays with biofilms (Pesce et al, 2011; Morin et al, 2012c; Kim Tiam et al, 2014b). Toxicity testing of pesticide extracted from POCIS was recently performed on biofilms originated from different French rivers subjected to agricultural pressure (Table 4).…”
Section: Introductionmentioning
confidence: 99%
“…The works based on the PICT concept, using PE considered as a “blackbox” of contaminants, allowed to highlight previous exposure of the biofilms, or not, to these cocktails. The ecological significance of combined PICT and PE approaches proved to be relevant, for biofilms sampled from rivers presenting different contamination profiles in term of concentrations and/or nature of compounds detected (Pesce et al, 2011; Morin et al, 2012c; Kim Tiam et al, 2014b; Foulquier et al, 2015). The PICT responses of field biofilms were compared in three study sites subjected to distinct kinds of agricultural pressure (increasing vineyard occupation from upstream to downstream in Morcille river, distinct land use along the Ruiné river and growing cereal crops at the Trec river; Table 4).…”
Section: Introductionmentioning
confidence: 99%